Production of Halal pheromone for perfumes from Salacca zalacca (salak) fruit - Rahman, Md. Mokhlesur; Raja Hussin, Tengku Mohammad Ariff; A.Latif, Ahmad Zubaidi; Mat So'ad, Siti Zaiton; Siddiqui, Jamshed; Awang, Mohamed; Yunus, Kamaruzzaman; Wan Nik, Wan Sani; Hilmi, Nur Nadhirah (2019)
Salacca zalacca (salak fruit) is a species of palm tree native to South west Java and North Sumatra in Indonesia. It has a reddish-brown scaly skin with pleasant pineapple, pear, and banana-like aromas combined. Due to its pleasant aroma, S .zalacca has potential in the halal perfumery and pharmaceutical industries. The volatile aromas of plants are usually extracted by conventional extraction methods such as steam distillation and solvent extraction methods. These methods are laborious, have incomplete extraction process, require long extraction time, and produced a lot of toxic chemical wastes. Solvent extraction methods mobile phase are mostly non-halal (alcoholic) solvents. New extraction technique supercritical fluid extraction (SFE) is introduced to overcome these limitations. SFE is considered a green extraction technique because it is renewable produces little nontoxic wastes, and has short extraction time. In this study,thevolatilearomaofS.zalaccawasextractedbysteamdistillation, solvents extraction with organic solvents and SFE. The efficiency and percentage yield of these extracts were compared.The percentage yields of SFE extracts were higher (10 MPa, 30°C:0. 2577%; 25MPa,30°C:0. 2675%;40 MPa,30°C:0.2721%) than the steam distillation (0.1855%),diethyl ether(0.5692%),hexane(0.0511%)and DSM(0.1358%) solvent extracts.However, SFE produced a lower yield (40MPa,300C:0 .2721%) than the diethyl ether solvent extraction (0.5692%)but SFE was found to be more efficient and environmentally-friendly. This aroma compound can be used for halal pheromone perfumes production.